Condition‐related predictors of successful transition from paediatric to adult care among adolescents with Type 1 diabetes. Issue 7 (30th March 2015) - Mistry, B.; Van Blyderveen, S.; Punthakee, Z.; Grant, C.
Abstract Aims To describe patient attendance for adult treatment after completion by young people of a structured Diabetes Transition Clinic and to identify the predictors of non‐attendance at adult clinics by young people with Type 1 diabetes transitioning from paediatric care. Methods Young people with Type 1 diabetes were consecutively enrolled on a Diabetes Transition Clinic programme at a Canadian paediatric teaching hospital, beginning in December 2007. Data from clinical interviews completed by an adolescent medicine specialist and an adult endocrinologist were prospectively collected at the Diabetes Transition Clinic visit in the patient's 18th year, before he/she was transferred at age 18 years to the adult clinic and at the first adult clinic visit. Results As of June 2011, 136 young people participating in the Diabetes Transition Clinic programme had been discharged from paediatric care at least 1 year earlier. Of these, 43 participants were lost to follow‐up. Loss to follow‐up was more frequent among: those who were diagnosed with diabetes before the age of 12 years; those who were taking insulin twice or three times daily rather than by pump or multiple daily injections; those who had higher HbA1c levels; those who had fewer diabetes physician visits in the year preceding the Diabetes Transition Clinic visit; and those who did not ask questions at the Diabetes Transition Clinic visit. Conclusions Several factors easily ascertained at a clinical encounter before transition can predict the likelihood of attendance in adult care, including age at diagnosis, mode of insulin administration, frequency of physician visits, and questions asked by patients during a transition visit.